Integrating livestock production and cultural tourism: Development strategy of Tok-Tok Sape on Bawean Island, Indonesia - Akhiroh, Puji; Ciptadi, Gatot; Budiarto, Agus; Hemiyanti, Adelina Ari; Andriani, Ria Dewi; Putri, Ardyah Irsanti R. (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Bawean Island, located in Gresik Regency, East Java, holds a unique cultural tradition in the form of Tok-Tok Sape bullfighting, where Bali and Madura cattle are specially raised for traditional contests. This study aims to analyze the production potential of livestock and the development prospects of Tok-Tok Sape as a cultural and ecotourism attraction. Methods: A survey method with structured questionnaires was used to collect primary data from cattle breeders in Tambak and Sangkapura sub-districts, complemented by observations, interviews, and microclimate measurements. Data were analyzed using descriptive statistics and SWOT analysis to identify strategic factors influencing development opportunities. Results: The SWOT analysis positioned Tok-Tok Sape ecotourism development in Quadrant I (coordinates 1.47; 0.73), indicating that internal strengths—including cultural uniqueness (5.12 points), active community participation, and high-quality cattle—significantly outweigh weaknesses, while external opportunities such as government support and rising tourist interest (4.48 points) present substantial potential. Based on these findings, an SO (Strengths-Opportunities) Strategy is recommended, which focuses on three key actions: (1) integrating Tok-Tok Sape into broader cultural tourism packages, (2) formalizing event management through professional training and infrastructure improvement, and (3) leveraging government support to promote Bawean cattle as a distinctive breed. The cultural event significantly enhances cattle market value by 20-30% and strengthens local identity. Conclusions: Implementing this strategy would not only support cultural preservation but also generate economic benefits for the local community, contributing to rural development and demonstrating how traditional practices can be aligned with sustainable tourism principles to foster community empowerment. The study reflects the importance of maximizing cultural assets through proactive development strategies that balance economic growth with heritage conservation.